2020
DOI: 10.3390/app10114052
|View full text |Cite
|
Sign up to set email alerts
|

Biostimulant Effect of Marine Macroalgae Bioextract on Pepper Grown in Greenhouse

Abstract: Marine macroalgae are a vast source of raw materials and biologically active molecules used in the pharmaceutical, cosmetic, food and agricultural industries. The search for a food free of chemical residues by consumers has led producers to use environmentally friendly and economically viable products as they are a source of natural compounds, forming a new and promising area of study. In this context, concentrated marine algae extracts (CMAEs) are an important alternative in this production model. This work a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Khan and collaborators [194] found that greenhouse grown pepper cultivars sprayed with ANE 'Wokozim' at 15-day intervals at the rate of 2 and 4 mL L −1 behaved differently, as the 'Sven Rz' cultivar showed an 83% increase in yields, whereas 'Red knight' showed a 46.4% increase, both compared to the respective untreated controls. More recent research conducted by Melo and collaborators [195] recorded in-between results by 'Elisa' peppers sprayed with a 0.5% solution of 'Reabilit Algas'. The mixture of Kappaphycus alvarezii and Sargasum vulgare increased the 1000 plant yield by an estimated 68.8%, compared to its untreated control.…”
Section: Implication Of Biostimulant Substance Treatments On Nightshade Green Growth and Fruit Yieldmentioning
confidence: 99%
“…Khan and collaborators [194] found that greenhouse grown pepper cultivars sprayed with ANE 'Wokozim' at 15-day intervals at the rate of 2 and 4 mL L −1 behaved differently, as the 'Sven Rz' cultivar showed an 83% increase in yields, whereas 'Red knight' showed a 46.4% increase, both compared to the respective untreated controls. More recent research conducted by Melo and collaborators [195] recorded in-between results by 'Elisa' peppers sprayed with a 0.5% solution of 'Reabilit Algas'. The mixture of Kappaphycus alvarezii and Sargasum vulgare increased the 1000 plant yield by an estimated 68.8%, compared to its untreated control.…”
Section: Implication Of Biostimulant Substance Treatments On Nightshade Green Growth and Fruit Yieldmentioning
confidence: 99%
“…The priming of plant seeds with seaweed extracts improved germination in a range of species. This is supported by the studies made on wheat (Kumar and Sahoo 2011;Hamouda et al 2022), maize (Matysiak et al 2011), pepper (Sivitepe and Sivritepe 2008), green gram (Kavipriya et al 2011), common bean (Carvalho et al 2013), barley (Mostek et al 2015), radish (Kasim et al 2016) and pepper (Melo et al 2020). Furthermore, Ahmed et al (2021) reported increased radish growth in soil polluted with heavy metals (Pb, Cu, Zn, and Ni) mixed with dried seaweeds as a result of nutrients and growth hormones present in the seaweeds, and concluded that seaweeds could be used in eco-friendly soil pollution bioremediation.…”
Section: Introductionmentioning
confidence: 81%
“…Biostimulants are natural compounds that enable plant growth, favoring plant tolerance to abiotic and biotic stresses [101]. The ability of macroalgae extract to act as biostimulants is the result of its composition in bioactive compounds, specifically those that are plant growth hormones; cytokinins, auxins, abscisic acid and gibberellins, among others [102].…”
Section: Macroalgae As Bio-resource For Biostimulants Productionmentioning
confidence: 99%